Implementasi dan Analisis Metode MOORA dan SMART pada pemilihan Platform Jual Beli Online menggunakan Decision Support System - Ramadhan, Rizal Furqan (Computer Engineering Departement, Universitas Komputer Indonesia, 2023)
Online buying and selling transactions have become a necessity and routine for generation Z in the era of technology 4.0. This phenomenon is an effect caused by the existence of the internet. The internet innovates for software developers to create communication applications without meeting face-to-face. Due to the rapid development of the internet, many online buying and selling platforms have emerged and are used by online shopping activists, especially generation Z. Of course, the various trading platforms have differences in appearance and usability. So it is necessary to research selecting the ideal platform using the Decision Support System as the data processing system. While the methods used are the MOORA and SMART methods, the two approaches will analyze the differences in the calculation results and the advantages of each technique. The results of the MOORA method are inversely proportional to the SMART method, but the difference is only that the difference in the final scores is not that great. Hence, the two approaches are ideal for a Decision Support System. Keywords – decision Support System, internet, jual beli, moora, smart.